Role of duodenal iron transporters and hepcidin in patients with alcoholic liver disease - Dostalikova-Cimburova, Marketa; Balusikova, Kamila; Kratka, Karolina; Chmelikova, Jitka; Hejda, Vaclav; Hnanicek, Jan; Neubauerova, Jitka; Vranova, Jana; Kovar, Jan; Horak, Jiri (Journal of cellular and molecular medicine, 2014)
Patients with alcoholic liver disease (ALD) often display disturbed iron indices. Hepcidin, a key regulator of iron metabolism, has been shown to be down-regulated by alcohol in cell lines and animal models. This down-regulation led to increased duodenal iron transport and absorption in animals. In this study, we investigated gene expression of duodenal iron transport molecules and hepcidin in three groups of patients with ALD (with anaemia, with iron overload and without iron overload) and controls. Expression of DMT1, FPN1, DCYTB, HEPH, HFE and TFR1 was measured in duodenal biopsies by using real-time PCR and Western blot. Serum hepcidin levels were measured by using ELISA. Serum hepcidin was decreased in patients with ALD. At the mRNA level, expressions of DMT1, FPN1 and TFR1 genes were significantly increased in ALD. This pattern was even more pronounced in the subgroups of patients without iron overload and with anaemia. Protein expression of FPN1 paralleled the increase at the mRNA level in the group of patients with ALD. Serum ferritin was negatively correlated with DMT1 mRNA. The down-regulation of hepcidin expression leading to up-regulation of iron transporters expression in the duodenum seems to explain iron metabolism disturbances in ALD. Alcohol consumption very probably causes suppression of hepcidin expression in patients with ALD.
Keywords: cytochromy typu b; DCYTB; dospělí; Female; gene expression; HEPH; iron; Adult; železo; alkoholické nemoci jater; ženské pohlaví; lidé; ferroportin; membránové proteiny; studie případů a kontrol; Aged, 80 and over; Ferroportin; Humans; HFE; hepcidiny; Male; Case-Control Studies; Aged; Iron; duodenum; Hepcidins; Oxidoreductases; Cation Transport Proteins; FPN1; oxidoreduktasy; Liver Diseases, Alcoholic; exprese genu; Membrane Proteins; proteiny přenášející kationty; lidé středního věku; alcoholic liver disease; senioři nad 80 let; senioři; mužské pohlaví; Duodenum; hepcidin; DMT1; Middle Aged; Gene Expression; TFR1; Cytochrome b Group